Low-temperature conversion of low-grade organic raw, part 2 (economic aspects); MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Kazakov A. V. Aleksandr Vladimirovich; Tabakaev R. B. Roman Borisovich; Novoseltsev P. Yu. Pavel Yurievich; Astafyev A. V. Aleksandr Vladimirovich (2014, 2014)
Title screen